Physics and chemistry-based constitutive modeling of photo-oxidative aging in semi-crystalline polymers. (15th March 2022) - Najmeddine, Aimane; Xu, Zhen; Liu, Gehui; Croft, Zacary L.; Liu, Guoliang; Esker, Alan R.; Shakiba, Maryam
Abstract: This paper proposes a physio-chemically-based constitutive framework to predict the response of severely photo-oxidatively aged semi-crystalline polymers. Photo-oxidation induced by the exposure to Ultra-Violet (UV) light and oxygen is one of the main and dominant degradation mechanisms affecting the lifespan of polymers. In this work, we first characterize the physio-chemical changes of low-density polyethylene (LDPE) to understand and map the photo-oxidation degradation process. Changes in crystallinity and mass loss are characterized by Differential Scanning Calorimetry (DSC) and Quartz Crystal Microbalance with Dissipation Monitoring (QCM-D) experiments, respectively. The evolution of crystallinity and mass loss relative to the initial pristine films over exposure time are considered as indicators of material degradation. Based on these tests, we then propose evolution functions for the material properties in the polymer constitutive equations to incorporate the effects of photo-oxidation on the mechanical responses. Connecting the physio-chemical processes affecting polymer network evolution to the mechanical response of LDPE eliminates the need for defining extra fitting parameters that carry no physical meaning. The developed constitutive framework is validated with respect to a series of in-house uniaxial tensile tests performed on LDPE aged for different UV exposure times. Validation of the proposed constitutive framework confirms the accuracy of DSC and QCM-D as rigorous techniques in the characterization of degradation in LDPE films, and confirms the robustness of the developed framework in predicting the mechanical responses of photo-oxidatively aged LDPE.